Strategy Analysis in Building Popularity on the Instagram Account @keanuagl: Analisis Strategi dalam Membangun Popularitas pada Akun Instagram @keanuagl - Prastyo, Muhammad Fajar Dicky; Pudjasetia, Faraby Al- Alirsyad; Febriana, Poppy (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the strategies used by the Instagram account @keanuagl in building popularity on social media platforms. As one of the public figures who has succeeded in attracting the attention of the audience in a relatively short time, this account is an interesting example to study, especially in the context of content strategy and interaction with followers. This study uses a qualitative approach with a content analysis method, observing upload patterns, types of content, and how the account interacts with the audience. The results show that the success of @keanuagl is influenced by several main factors, such as consistency in uploads, use of humor and personal narratives, and collaboration with other public figures. In addition, the use of interactive features such as Stories, Live, and comments also contribute to increasing follower engagement. This study provides insight into how social media strategies can be used effectively to build popularity and strengthen relationships with audiences in the digital era. This study analyzes the strategy of the Instagram account @keanuagl in building popularity. With a qualitative approach and content analysis, the study observed upload patterns, types of content, and interactions with followers. The results show that consistency of uploads, use of humor, personal narratives, and collaboration with other public figures are the main factors. The use of interactive features such as Stories and Live also increases follower engagement. This study shows the effectiveness of social media strategies in building popularity in the digital era. Highlights: Content Strategy – Consistent uploads, engaging humor, and personal narratives help attract and retain followers. Audience Interaction – Features like Stories, Live, and comments enhance engagement and strengthen relationships with followers. Collaborations – Partnering with other public figures expands reach and boosts visibility on social media. Keywords: Popularity, Instragram, Personal Branding